Effects of short-term orlistat therapy on maximal power production capacity in obese patients - Özçelik, O?uz; Çolak, Ramis; Türko?lu, A. Baki (My University, 2002)
The aim of this study was to examine the effects of weight loss induced by hypocaloric diet and orlistat therapy for a four-week period on maximal work rate (Wmax) production capacity and aerobic fitness in obese patients. Fifteen obese subjects were given an integrated energy restricted diet and orlistat supplement (DO). Each patient performed two incremental ramp exercise tests using an electromagnetically braked cycle ergometer: one at the beginning and one at the end of the four-weeks to determine Wmax production capacity. Four weeks of DO therapy resulted in a significant reduction in total body weight (93.7 ± 14.6 kg vs. 90.3 ± 13.5 kg. P = 0.0001) and body fat mass (37.8 ± 6.4 kg vs. 35.9 ± 7.1 kg, P = 0.003). However. weight reduction achieved during DO therapy was not associated with increased Wmax production capacity: 100 ± 31 W (basal) vs. 103 ± 31 W (four-week) (P = 0.3) and aerobic fitness: 69.2 ± 19 W (basal) vs 66.7 ± 19 W (four-week) (P = 0.5). Body weight reduction without improving obese patients' Wmax production capacity during the DO therapy period indicates that physicians should consider an exercise training program, which is expected to improve obese patients' functional capacity.
Keywords: Body mass index; Obesity; Orlistat; Weight loss